Drugs for the treatment of peripheral neuropathies. (11th February 2016) - Marmiroli, Paola; Cavaletti, Guido
ABSTRACT: Peripheral neuropathies are frequent in association with systemic diseases as well as isolated disorders. Recent advances in the therapy of specific neuropathies led to the approval of new drugs/treatments. This review selected those peripheral neuropathies where the most recent approvals were provided and revised the potential future developments in diabetic and toxic-induced neuropathies, although they do not have a currently available causal therapy in view of their epidemiological and social relevance. Data have been extracted from the most important published trials and from clinical experience. In addition, data from the Food and Drug Administration and European Medicine Agency indications on the treatment of the selected peripheral neuropathies and from recently updated international guidelines have also been included. The website of the U.S. National Institutes of Healthwww.clinicaltrials.gov registry has been used as the reference database for phase III clinical trials not yet published or ongoing. This review gives a general overview of the most recent advances in the treatment of amyloid, inflammatory, and paraproteinemic peripheral neuropathies. Moreover, it briefly describes the unmet medical need in disabling and frequent conditions, such as diabetic and chemotherapy-induced neuropathy, highlighting the most promising therapeutic approaches to their treatment.